Simplifying and extending the AdS(5) x S-5 pure spinor formalism - Berkovits, Nathan [UNESP] (Springer, 2009)
Although the AdS(53) x S-5 worldsheet action is not quadratic, some features of the pure spinor formalism are simpler in an AdS(5) x S-5 background than in a flat background. The BRST operator acts geometrically, the left and right-moving pure spinor ghosts can be treated as complex conjugates, the zero mode measure factor is trivial, and the b ghost does not require non-minimal fields.Furthermore, a topological version of the AdS(5) x S-5 action with the same worldsheet variables and BRST operator can be constructed by gauge-fixing a GIG principal chiral model where G = PSU(2,2|4). This topological model is argued to describe the zero radius limit that is dual to free N = 4 super-Yang-Mills and can also be interpreted as an "unbroken phase" of superstring theory.
Keywords: AdS-CFT Correspondence; Topological Strings